Analisis Dampak Kebakaran Hutan dan Kebun terhadap Distribusi Pendapatan Masyarakat di Kabupaten Ogan Komering Ilir - Hakekat, Azom; Lisdiana, Lisdiana; Asteriniah, Femi (@-Publik: Jurnal Administrasi Publik, 2023)
This study aims to analyze the impact of forest and garden fires on the distribution of com-munity’s income in Ogan Komering Ilir Regency. This research shows that: (1) There is a social impact caused by Forest and Garden Fires on the people in Ogan Komering Ilir Regency. The thick smoke caused people to stay at home and were not able to carry out activities outdoors. Forest and garden fires also impacted the tradition of menganyam purun because the raw mate-rials are hard to find. The crime rate has increased because of the limited options on employy-ment, so people needed to make ends meet in any way possible, including by committing to theft and other crime acts. (2). On the dimension of economic impact, the forest fires lowered the field of jobs. In addition, the large scale of the forest fires in OKI District hindered the commu-nity from conducting economic transactions. Forest fires also cause a reduction in garden yields and agricultural activities. The smoke caused by burning forests prevents people from working in their fields and gardens. In addition, forest fires cause plants to wilt because they did not get enough sunlight.